Gallium isotope fractionation during Ga adsorption on calcite and goethite. (15th February 2018) - Yuan, Wei; Saldi, Giuseppe D.; Chen, JiuBin; Vetuschi Zuccolini, Marino; Birck, Jean-Louis; Liu, Yujie; Schott, Jacques
Abstract: Gallium (Ga) isotopic fractionation during its adsorption on calcite and goethite was investigated at 20 °C as a function of the solution pH, Ga aqueous concentration and speciation, and the solid to solution ratio. In all experiments Ga was found to be enriched in light isotopes at the solid surface with isotope fractionation △ 71 Gasolid-solution up to −1.27‰ and −0.89‰ for calcite and goethite, respectively. Comparison of Ga isotopic data of this study with predictions for 'closed system' equilibrium and 'Rayleigh fractionation' models indicates that the experimental data are consistent with a 'closed system' equilibrium exchange between the fluid and the solid. The results of this study can be interpreted based on Ga aqueous speciation and the structure of Ga complexes formed at the solid surfaces. For calcite, Ga isotope fractionation is mainly triggered by increased Ga coordination and Ga–O bond length, which vary respectively from 4 and 1.84 Å in Ga(OH)4 − to 6 and 1.94 Å in the >Ca–O–GaOH(OH2 )4 + surface complex. For goethite, despite the formation of Ga hexa-coordinated >FeOGa(OH)2 0 surface complexes (Ga–O distances of 1.96–1.98 Å) both at acid and alkaline pH, a similar extent of isotope fractionation was found at acid and alkaline pH, suggesting that Ga(OH)4 − is preferentially adsorbed on goethite for all investigated pH conditions. In addition, the observed decrease of Ga isotope fractionation magnitude observed with increasing Ga surface coverage for both calcite and goethite is likely related to the formation of Ga surface polymers and/or hydroxides with reduced Ga–O distances. This first study of Ga isotope fractionation during solid-fluid interactions suggests that the adsorption of Ga by oxides, carbonates or clay minerals could yield significant Ga isotope fractionation between secondary minerals and surficial fluids including seawater. Ga isotopes thus should help to better characterize the surficial biogeochemical cycles of gallium and its geochemical analog aluminum.